2017
DOI: 10.1111/bph.14031
|View full text |Cite
|
Sign up to set email alerts
|

Tetrandrine antagonizes acute megakaryoblastic leukaemia growth by forcing autophagy‐mediated differentiation

Abstract: Modulating autophagy-mediated differentiation may be a novel strategy for treating AMKL, and tetrandrine has the potential to be developed as a differentiation-inducing agent for AMKL chemotherapy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
27
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 34 publications
(28 citation statements)
references
References 57 publications
(57 reference statements)
0
27
0
Order By: Relevance
“…Many monomers extracted from traditional Chinese medicine have inhibitory effects on osteoclastogenesis (Chen et al, 2017). Tetrandrine, a bis-benzylisoquinoline alkaloid isolated from Stephania tetrandra S Moore and other Chinese herbs, has been shown to have anti-inflammatory, antineoplastic, immunologic, and antiallergenic effects (Mei et al, 2015;Liu et al, 2017;Yu et al, 2018;Jia et al, 2019). Clinically, it has been widely used in the treatment of rheumatoid arthritis.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Many monomers extracted from traditional Chinese medicine have inhibitory effects on osteoclastogenesis (Chen et al, 2017). Tetrandrine, a bis-benzylisoquinoline alkaloid isolated from Stephania tetrandra S Moore and other Chinese herbs, has been shown to have anti-inflammatory, antineoplastic, immunologic, and antiallergenic effects (Mei et al, 2015;Liu et al, 2017;Yu et al, 2018;Jia et al, 2019). Clinically, it has been widely used in the treatment of rheumatoid arthritis.…”
Section: Discussionmentioning
confidence: 99%
“…Tetrandrine, a bis-benzylisoquinoline alkaloid, has been isolated from Stephania tetrandra S Moore, and other Chinese herbs. Previous studies have demonstrated that tetrandrine has antiinflammatory, antineoplastic, immunologic, and antiallergenic effects, and it has been widely used clinically in the treatment of rheumatoid arthritis (Wang et al, 2004;Liu et al, 2017;Yu et al, 2018). PMOP has a strong correlation with rheumatoid arthritis considering inflammatory cytokines played key roles in both of them.…”
Section: Introductionmentioning
confidence: 99%
“…Tetrandrine has broad-spectrum antitumor effects (Bhagya and Chandrashekar 2018;Liu 2017;Liu et al 2016) in many types of cancer cells, including human liver cancer (Zhang et al 2018a;Yu and Ho 2013), osteosarcoma Lu et al 2017), oral cancer (Lien et al 2017;Huang et al 2013), colon carcinoma (Meng et al 2004;Li et al 2019), gastric cancer (Bai et al 2018;Qin et al 2013), brain glioblastoma multiforme GBM 8401 cancer (Jiang et al 2019) and lung carcinoma (Chow et al 2018;Cho et al 2009). It also exhibits antineoplastic activity against gallbladder carcinoma (Zhu et al 2014), thyroid carcinoma B-CPAP cells ), prostatic carcinoma PC3 cells (Lan et al 2018), esophageal cancer , breast cancer (Guo and Pei 2019), pancreatic cancer (Singh et al 2018), nasopharyngeal carcinoma (Lin et al 2016(Lin et al , 2017b, acute megakaryoblastic leukemia (Liu et al 2017c), cervical cancer (Zhang et al 2018b) and renal carcinoma (Chen et al 2014(Chen et al , 2017a cells. Although tetrandrine exhibited broad anti-tumor effects, a number of these studies lacked positive controls or anti-tumor evaluation of tetrandrine in vivo.…”
Section: Anti-inflammatory Effectsmentioning
confidence: 99%
“…Our previous studies have indicated that tetrandrine induced apoptosis at a high concentration and induced autophagy at low concentrations [ 10 12 ]. Moreover, tetrandrine showed potential anti-tumor activity in leukemia and hepatocellular carcinoma [ 13 , 14 ].…”
Section: Introductionmentioning
confidence: 99%